Reakce na kovy u pacientů s chronickou únavou a autoimunitními endokrinopatiemi - Sterzl, I; Hrdá, P; Procházková, J; Bártová, J; Matucha, P (Vnitrni lekarstvi, 1999)
Our study was designed to assess the effect of heavy metals on the severity of fatigue in autoimmune thyroid disease associated with autoantibodies against other endocrine organs. We compared our data with those obtained from other groups of patients. A total of five groups of patients were examined by their medical history, dental examination, and using a modified test of blast transformation of metals (Melisa): a) 10 fatigues female patients with autoimmune thyroidism and polyglandular activation of autoimmunity, b) 12 fatigued patients with autoimmune thyroidism, c) 28 fatigued patients free of endocrinopathy, d) 22 professionals without evidence of autoimmunity, e) 13 controls, a population sample, the individuals did not complain of marked fatigue and their laboratory tests did not show signs of autoimmunity and endocrinopathy. Fatigue regardless of the underlying disease is primarily associated with hypersensitivity to inorganic and organic mercury, nickel, and gold. The groups differed in their hypersensitivity to other metals. In the control group, hypersensitivity--mostly to cadmium and lead--was found in four of the examined individuals only. Statistical analysis of data obtained from professionals and controls revealed a higher incidence of positivity to organic and inorganic mercury and nickel in professionals.
Keywords: dospělí; syndrom chronické únavy; Female; Fatigue Syndrome, Chronic; Adult; Allergens; ženské pohlaví; Lymphocyte Activation; alergie; aktivace lymfocytů; lidé; autoimunitní tyreoiditida; Thyroiditis, Autoimmune; Hypersensitivity; Male; těžké kovy; alergeny; lidé středního věku; mužské pohlaví; Metals, Heavy; Middle Aged; Humans